Statins for primary prevention of cardiovascular (CV) events. Issue 5 (May 2017) - Shungu, Nicholas
Abstract : N/A: Yusuf S, Bosch J, Dagenais G, et al. Cholesterol lowering in intermediate‐risk persons without cardiovascular disease. N Engl J Med . 2016; 374(21):2021–2031.